Arteriovenous fistula creation in a patient without a pulse: Vascular access in patients with left ventricular assist devices. Issue 6 (November 2019) - Khawaja, Aurangzaib; Lim, Hoong Sern; Howell, Neil J; Inston, Nicholas
Left ventricular assist devices are used in heart failure patients as bridge to transplantation or increasingly as a destination therapy. These patients frequently have renal dysfunction and many reach end-stage renal failure. If haemodialysis is required, minimization of infection risk is essential. Arteriovenous grafts have been recommended for these patients due to hypothetical concerns regarding fistula maturation due to continuous flow. A case is described where a brachiocephalic arteriovenous fistula was successfully formed and used for dialysis without issue. This is one case of a small number in the literature where arteriovenous fistulas have been used in left ventricular assist device patients and it appears that concerns are unfounded and good outcomes have been reported. It would appear from this experience that approaches to vascular access for dialysis in patients with continuous-flow left ventricular assist devices are in accordance with vascular access guidelines and standard practice.